2019
DOI: 10.1186/s12958-019-0556-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of diagnostic biomarkers in patients with gestational diabetes mellitus based on transcriptome gene expression and methylation correlation analysis

Abstract: BackgroundGestational diabetes mellitus (GDM) has a high prevalence in the period of pregnancy. However, the lack of gold standards in current screening and diagnostic methods posed the biggest limitation. Regulation of gene expression caused by DNA methylation plays an important role in metabolic diseases. In this study, we aimed to screen GDM diagnostic markers, and establish a diagnostic model for predicting GDM.MethodsFirst, we acquired data of DNA methylation and gene expression in GDM samples (N = 41) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 42 publications
(43 reference statements)
0
15
0
Order By: Relevance
“…This is illustrated by a study on modeling GA [114] using stacked generalization [115] to integrate biological signals across seven different omics. In another study, the incorporation of transcriptomic and epigenetic data was shown to increase performance in the identification of GDM in addition to helping in the elucidation of its biological basis [116]. However, the individual characteristics of different omics as well as their inherent differences in numbers of features (e.g., sparse microbiome data versus targeted proteomics assays) pose unique challenges for their integration into statistical models.…”
Section: Box 2 Machine Learning: Supervised Learningmentioning
confidence: 99%
“…This is illustrated by a study on modeling GA [114] using stacked generalization [115] to integrate biological signals across seven different omics. In another study, the incorporation of transcriptomic and epigenetic data was shown to increase performance in the identification of GDM in addition to helping in the elucidation of its biological basis [116]. However, the individual characteristics of different omics as well as their inherent differences in numbers of features (e.g., sparse microbiome data versus targeted proteomics assays) pose unique challenges for their integration into statistical models.…”
Section: Box 2 Machine Learning: Supervised Learningmentioning
confidence: 99%
“…As a widely applied machine learning algorithm, SVM is reported to be used in the investigation of GDM. It has been reported that SVM is applied in the identification of diagnostic biomarkers in patients with GDM based on transcriptome gene expression and methylation analysis [ 7 ]. The artificial immune recognition system and SVM model contribute to predicting GDM [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the progression of GDM has been investigated for decades, the practical and well-designed diagnostic models for the clinical prediction of GDM are extremely limited [ 6 ]. Therefore, it is essential to find effective biomarkers for improving the diagnosis and alleviating the adverse pregnancy outcomes of GDM [ 7 , 8 ]. However, the advancement of this research field is still poor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been used in identifying the chemical perturbagens capable of intervening the critical molecular pathways in diseased conditions. For example, the genomics and transcriptomics data profiling has helped in elucidating the pathogenesis of diabetes (15)(16)(17) and in identifying potential new mechanisms in DN (18,19). However, there are only a few studies that shed light on the potential pathogenesis mechanism and cross-talks between GDKD, TDKD and early diabetic nephropathy (EDN).…”
Section: Introductionmentioning
confidence: 99%